2008
DOI: 10.1371/journal.pone.0003617
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene Signature for Molecular Diagnosis of Human Prostate Cancer by RT-qPCR

Abstract: BackgroundProstate cancer (CaP) is one of the most relevant causes of cancer death in Western Countries. Although detection of CaP at early curable stage is highly desirable, actual screening methods present limitations and new molecular approaches are needed. Gene expression analysis increases our knowledge about the biology of CaP and may render novel molecular tools, but the identification of accurate biomarkers for reliable molecular diagnosis is a real challenge. We describe here the diagnostic power of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 55 publications
1
26
0
2
Order By: Relevance
“…[40][41][42][43] The mRNA signals were normalized to GAPDH mRNA internal control and the primers used are presented in the Table S1. Mir 25, miR93 and mir106b were analyzed by QRT-PCR by using specific RT-PCR primers from Applied Biosystem, Inc.…”
Section: Methodsmentioning
confidence: 99%
“…[40][41][42][43] The mRNA signals were normalized to GAPDH mRNA internal control and the primers used are presented in the Table S1. Mir 25, miR93 and mir106b were analyzed by QRT-PCR by using specific RT-PCR primers from Applied Biosystem, Inc.…”
Section: Methodsmentioning
confidence: 99%
“…A measure of 150 ng of cDNA was used to quantify and compare the transcript levels among the above-mentioned cell lines. ABI Step-One apparatus and Power SYBR Green Master Mix with primers were directed against human p21, p27, and GAPDH mRNA (Rizzi et al, 2008;Wakimoto et al, 2008;Vivar et al, 2009). The samples were analyzed with a standard 2-h run with an annealing temperature of 55 1C.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…In different kinds of cancers, CLU has been reported to be up-or down-regulated (Redondo et al 2000, Xie et al 2002, Zhang et al 2003, Chen et al 2004, Pucci et al 2004. We have found that CLU mRNA and protein products are down-regulated in both low-grade and high-grade prostate cancer (Bettuzzi et al 2000, Scaltriti et al 2004a, Rizzi et al 2008. The study was conducted in surgical prostate specimens from patients affected by prostatic adenocarcinoma graded from 1 to 5 (Scaltriti et al 2004a).…”
Section: Clu Expression In Prostate and Breast Cancermentioning
confidence: 99%